Conductometric determination of naproxen in bulk and pharmaceutical dosage form - Alhazmi, Hassan Ahmad; Al Bratty, Mohammed (European Journal of Chemistry, 2017)
This study aimed at the development of simple and cheap conductometric method that can be used for the determination of naproxen in bulk and dosage forms. During the study, naproxen was titrated with sodium hydroxide (Method A) and potassium hydroxide (Method B) and the end points were determined with conductivity cell. Variables affecting the end point determination were also studied in the range of 1-10 mg/mL of naproxen. The proposed methods were validated by precision and recovery studies. The percentage recoveries ranged from 99.15±0.659 and 101.13±0.543 with % RSD of 0.897 and 0.749 with sodium hydroxide and potassium hydroxide, respectively. The methods were effectively applied for the determination of naproxen in tablet dosage form. The methods proposed in this study can be used as substitute for more composite and classy methods used for the determination of naproxen and are highly reproducible as compared to other reported methods.